Drgania prętów o nieciągłych własnościach - CEMPEL, Czesław (Engineering Transactions, 1970)
Vibrations of the rods with discontinuous properties In this paper are solved the vibrations of the rods with step variable sections, concentrated mass and elasticity. Writing the motion of the rod by means of a distributive differential equation, eigenfunctions correct as to total lengths of the rod was obtained. Examples of the frequency equations so calculated are identical with the same obtained by application of continuity conditions.